Cross-media response to digital manipulation of still and moving images. - Gladney, George Albert; Ehrlich, Matthew C. (Journal of Broadcasting & Electronic Media)
This investigation provides survey data for a cross-media comparison between newspaper photo editors and television news directors to assess the ethical response to digital image processing and enhancement technology. The results indicate that television news directors tend toward less strict ethical standards in application of the technology. However the television people showed more sensitivity to aspects of the technology that relate to long-standing themes of TV critics. Reprinted by permission of the publisher.